2012
DOI: 10.1002/psc.2438
|View full text |Cite
|
Sign up to set email alerts
|

S‐ to N‐Acyl transfer in S‐acylcysteine isopeptides via 9‐, 10‐, 12‐, and 13‐membered cyclic transition states

Abstract: S-Acyl cysteine peptides containing α-, β- or γ-amino acid residues undergo long-range S- to N-acyl transfer to give analogs of native tripeptides and tetrapeptides containing additional carbon atoms in the chain. The ease of intramolecular S → N-acyl transfer relative to intermolecular transacylation is favored increasingly for 9 < 12 < 13 ~ 10-membered cyclic transition states; the observed order is explained on conformational and intermolecular interaction considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Internal Cys residues were reported to accelerate native chemical ligation (see Section 2.3.1), an especially selective approach for N-terminal cysteine conjugation, via cyclic transition states. [433][434][435][436][437][438]…”
Section: Fig 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Internal Cys residues were reported to accelerate native chemical ligation (see Section 2.3.1), an especially selective approach for N-terminal cysteine conjugation, via cyclic transition states. [433][434][435][436][437][438]…”
Section: Fig 20mentioning
confidence: 99%
“…Internal Cys residues were reported to accelerate native chemical ligation (see Section 2.3.1), an especially selective approach for N-terminal cysteine conjugation, via cyclic transition states. [433][434][435][436][437][438] 1.4 Tryptophan Tryptophan (Trp, W) is the second (after cysteine) low abundance amino acid with about 1% frequency (depending on the living organism), 235 but approximately 90% of proteins contain at least one Trp residue in their sequence. 439 The specific reactivity of tryptophan in proteins is one of the most challenging problems in bioconjugation.…”
Section: Fig 20mentioning
confidence: 99%
“…Several experimental and computational studies examined long-range S , N -acyl transfers for clarifying the relationships between the size of the cyclic transition state, i.e., the number of residues separating the Cys from the α-amino group, and the efficacy of acyl transfer. One important motivation for these studies was to define the synthetic scope for such acyl transfers. Another question of interest was to know if these macrolactamization reactions follow the classical tendency for macrolactonization that was reported in a series of seminal papers. In this classical picture of reaction rate versus ring size formation, macrolactonization proceeds at the fastest reaction rate via 5- and 6-membered ring transition states .…”
Section: Ncl Beyond Cys and Sec Junctionsmentioning
confidence: 99%
“…Katritzky and co-workers studied the reactivity of various Sacyl isopeptides containing internal S-acylated cysteine units with increasing chain lengths. [657][658][659][660][661]664 These isopeptides covered macrocyclic TSs upon S,N-acyl migrations with i ranging from 8 to 20 and constitute good mimics of the thioester-linked intermediate formed in the capture step during internal Cys-assisted ligations. The studies with S-acyl isopeptide Gly-Cys(Cbz-Ala)-OH (i = 8) or β-Ala-Cys(Cbz-Ala)-OH (i = 9) showed that the S,N-acyl migration proceeding through an 8-or 9-membered ring is highly disfavored.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…1a), to activate these pro-sensors. [11][12][13][14] These pro-sensors were synthesized using a common scheme (Scheme S1, ESI †), and differ in the aryl unit attached to the amine end of L-alanine. While Ph-amn contains a phenylacetyl unit, Nap-amn contains a 1-naphtheleneacetyl residue protecting the amine end of L-alanine.…”
mentioning
confidence: 99%